Catalytic bi-reforming of methane for carbon dioxide ennoblement. (February 2020) - Cunha, A.F.; Mata, T.M.; Caetano, N.S.; Martins, A.A.; Loureiro, J.M.
Abstract: New processes that may reduce the net carbon emissions and contribute to a more circular economy are needed. Bi-reforming of methane (BRM) is a promising method for syngas production, with a hydrogen-to-carbon monoxide ratio of two in the reaction products, relevant for example when the purpose is methanol synthesis. In this work, reaction studies were carried out over a nickel-based catalyst varying the temperature (798–1123 K). Three main temperature zones have been identified; a low temperature zone where the conversion of carbon dioxide is almost null, a middle temperature range where steam reforming of methane (SRM) is dominant while the conversion of carbon dioxide via dry reforming of methane (DRM) is low, and finally a high temperature range where DRM becomes more significant. The results show that syngas can be successfully produced using this process. For the range of operating conditions studied, the carbon dioxide and methane conversions increase with temperature, reaching 40% and 100%, respectively at the largest temperature studied. However, the production of syngas in a molar ratio of 1:2 for CO-to-H 2 requires the use of high temperatures. Most probably the nickel agglomerates on top of the γ -alumina support are responsible for the poor catalyst performance.